Molecular detection and genotype diversity of hemoplasmas in non-hematophagous bats and associated ectoparasites sampled in peri-urban areas from Brazil - Ikeda, Priscila [UNESP]; Torres, Jaire Marinho; Lourenço, Elizabete Captivo; Albery, Gregory F.; Herrera, Heitor Miraglia; de Oliveira, Carina Elisei; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2022)
Hemoplasmas have already been detected in bats in the United States of America, Spain, Australia, Chile, Brazil, Peru, Belize, Nigeria, Costa Rica, Germany, Switzerland and New Caledonia. The recent detection of hemoplasmas closely related to Mycoplasma haematohominis, an agent causing disease in humans, emphasizes the need for additional studies on the diversity of hemoplasmas in bats. The present work aimed to investigate the occurrence and assess the phylogenetic positioning and genetic diversity of hemoplasmas in bats and associated ectoparasites sampled in central-western Brazil. Overall, 43% (58/135) sampled bats and 1.56% (1/64) bat flies (Megistopoda aranea) were positive for hemoplasmas, however, twenty-four and two hemoplasma sequences were obtained from PCR assays targeting 16S and 23S rRNA genes, respectively, since the majority of the obtained amplicons showed faint bands in agarose gel electrophoresis. The obtained 16S rRNA sequences showed to be broadly distributed along the phylogenetic tree, albeit positioned within the ‘Haemofelis group’ and clustering with other bat-associated hemoplasmas. Twelve 16S rRNA hemoplasma genotypes were found among the 24 obtained sequences. When compared to other bat-related hemoplasmas sequences retrieved from the Genbank, 52 genotypes were found. The two 23S rRNA sequences obtained were positioned as a sister clade to “Candidatus Mycoplasma haematohydrochaerus”, M. haemofelis and M. haemocanis. High genetic diversity was found among 16S rRNA hemoplasma sequences detected in non-hematophagous bats from central-western Brazil and previously detected in other regions of the world. Even though the genotype analysis showed that hemoplasmas from the same genus tend to group together, the results from the unipartite and bipartite analyses did not robustly support the hypothesis. Further studies addressing the specificity of hemoplasma genotypes according to bat species and genera should be performed.
Keywords: 16S rRNA; 23S rRNA; Chiroptera; Genetic diversity; Hemoplasmas